2018
DOI: 10.3389/fonc.2018.00443
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden and Palliative Referral Disparities in an Ambulatory South Texas Cancer Center

Abstract: Background: The American Society of Clinical Oncology's recommendation for “dedicated palliative care services, early in the disease course, concurrent with active treatment” for cancer patients is a challenge for cancer centers to accommodate. Despite demonstrated benefits of concurrent care, disparities among socioeconomic and ethnic groups in access to supportive care services have been described. The aim of this project was to evaluate: (a) how insurance coverage and ethnicity impact patient symptom burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Perceived time to death or death acting as a mediator on the relationship between race and receipt of IPCC may contribute to the mixed findings of the association between race and IPCC in the literature. [21][22][23][24][25][26] Although several studies have found higher odds of IPCC for hospitalized black patients with cancer, a few have found no difference or higher odds of IPCC for black patients compared to white patients. [21][22][23][24][25][26] However, only one of these studies investigated death as a mediator of receipt of IPCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived time to death or death acting as a mediator on the relationship between race and receipt of IPCC may contribute to the mixed findings of the association between race and IPCC in the literature. [21][22][23][24][25][26] Although several studies have found higher odds of IPCC for hospitalized black patients with cancer, a few have found no difference or higher odds of IPCC for black patients compared to white patients. [21][22][23][24][25][26] However, only one of these studies investigated death as a mediator of receipt of IPCC.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Although several studies have found higher odds of IPCC for hospitalized black patients with cancer, a few have found no difference or higher odds of IPCC for black patients compared to white patients. [21][22][23][24][25][26] However, only one of these studies investigated death as a mediator of receipt of IPCC. 25 The absence of measurement of the potential mediator of death could explain the differences among these studies as highlighted by our findings of a transposed relationship between black race and IPCC when stratified by death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After searching almost fourthly-thousand citations, 284 articles were included in our study, of which 147 were manuscripts that directly addressed end-of-life and hospice care, palliative care, as well as advance care planning and directives that include non-Hispanic Blacks. 4 …”
Section: Methodsmentioning
confidence: 99%
“…20 In addition to its clinical significance, the ESAS has also been used as a trigger for referrals to specialized palliative care services. 6,21,22 Recently, a study found that patient exposure to the ESAS (measured by completing the ESAS at least once) was associated with improved survival in cancer patients. 23 While numerous studies have assessed the validity, clinical significance, and usability 7,12,13,16 of the ESAS, fewer studies have examined the patient experience surrounding the ESAS.…”
Section: Introductionmentioning
confidence: 99%